Overview of Phacidiales, including Aotearoamyces gen. nov. on Nothofagus - Luis Quijada; Peter R. Johnston; Jerry A. Cooper; Donald H. Pfister (IMA Fungus)
Abstract The new genus Aotearoamyces is proposed to accommodate a single species that was repeatedly collected on fallen wood in Nothofagaceae forests of New Zealand and was previously misidentified as a Claussenomyces species. This monotypic genus belongs to Tympanidaceae, a recently erected family in Phacidiales. Aotearoamyces is differentiated from other Tympanidaceae by phragmospores that do not form conidia either in or outside the asci, an exciple of textura intricata with hyphae widely spaced and strongly gelatinized (plectenchyma), and apically flexuous. partly helicoid paraphyses. The asexual morph was studied in pure culture. Phylogenetic analyses of combined SSU, ITS and LSU sequences strongly support a sister relationship between the sexually typified Aotearoamyces and the asexually typified “Collophorina” paarla characterized morphologically by forming endoconidia, a feature not found in the genetically distinct type species of Collophorina. Based on our molecular results, we place the genus Epithamnolia in the Mniaecia lineage within Phacidiales.